2016
DOI: 10.1017/s104161021600034x
|View full text |Cite
|
Sign up to set email alerts
|

Facial emotion recognition and its relationship to cognition and depressive symptoms in patients with Parkinson's disease

Abstract: The present investigation yields further evidence for impaired FER in PD. Interestingly, our data suggest FER deficits even in cognitively intact PD patients indicating FER dysfunction prior to the development of overt cognitive dysfunction. Age showed a negative association whereas IQ showed a positive association with FER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…As authors who assessed cognitive abilities used different tests measuring different aspects of executive function, no consistent conclusion could be drawn regarding the link between cognitive impairement and FER in PD 21, 32, 36, 45, 48, 56, 94. In recent studies,21, 22, 26, 29, 45, 95 however, an FER deficit was confirmed among patients after controlling for cognitive symptoms (including working memory and attention processes) but seemed to be influenced by their magnitude.…”
Section: Discrepancies In Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As authors who assessed cognitive abilities used different tests measuring different aspects of executive function, no consistent conclusion could be drawn regarding the link between cognitive impairement and FER in PD 21, 32, 36, 45, 48, 56, 94. In recent studies,21, 22, 26, 29, 45, 95 however, an FER deficit was confirmed among patients after controlling for cognitive symptoms (including working memory and attention processes) but seemed to be influenced by their magnitude.…”
Section: Discrepancies In Resultsmentioning
confidence: 99%
“…Indeed, about 30% of the reviewed studies did not examine its effect on the recognition of specific emotions but calculated an overall score encompassing all the displayed emotions 4, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29. Moreover, authors did not manipulate the same set of stimuli, and some only used a small subset 23, 30, 31, 32, 33, 34, 35.…”
Section: Facial Emotion Recognition In Pdmentioning
confidence: 99%
“…Impairments of facial emotion recognition in PD patients were found to be independent of depressive symptoms [ 167 , 179 - 181 ], executive deficits [ 179 , 180 ], and clinical aspects (i.e., disease duration and severity, [ 180 ]). Moreover, some studies revealed that emotion recognition abnormalities may occur after subthalamic nucleus stimulation [ 182 - 185 ], probably due to alterations of projections to cortical areas, particularly the OFC, which has been already implicated in emotion recognition [ 186 ].…”
Section: Social Cognition Abnormalities In Neurodegenerative Disormentioning
confidence: 99%
“…In the context of non-motor symptoms (NMS) in PD, impairments in facial emotion recognition have constantly been a matter of debate ( Pietschnig et al, 2016 ; Assogna et al, 2008 ; Gray and Tickle-Degnen, 2010 ; Dujardin et al, 2004 ; Ibarretxe-Bilbao et al, 2009 ). Hereby, several studies reported deficits in PD patients in the recognition of fear and/or sadness ( Ariatti et al, 2008 ; Martinez-Corral et al, 2010 ; Saenz et al, 2013 ), others revealed impairments in the recognition of anger and/or disgust ( Martinez-Corral et al, 2010 ; Clark et al, 2010 ; Lawrence et al, 2007 ; Suzuki et al, 2006 ; Clark et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%